Effects of Periparturient Anthelmintic Treatment on the Milk Yield in Cows - Md. Faruk Islam; Begum Fatema Zohara; Nurjahan Begum; Md. Golam Shahi Alam (The Korean Society of Animal Reproduction and Biotechnology, 2014)
This study was conducted to determine the efficacy of anthelmintics against gastrointestinal parasitic infestation in periparturient dairy cows and its effect on milk yield and quality. Sixty pregnant cows of 1st & 2nd parity were divided into four groups. The efficacy of anthelmintic treatment was evaluated by counting faecal egg per gram (EPG) compared with pre-treatment values. The milk yield of each cow was recorded in pre and post treatment lactations. Cows of group A were treated with Nitroxynil 10 mg/kg body weight subcutaneously 30 days before parturition, group B were treated with combination of triclabendazole and levamisole 19.5 mg/kg body weight orally at calving and group C treated with Endex® at calving and 42 days after. The mean change in EPG 14 days after treatment was significantly higher (p<0.05) in treated (79.1%) cows than control. Average milk yield of group C (2.8 ± 0.8) was significantly higher (p<0.01) than group A (2.6 ± 0.7). Similarly, the average milk yield in all the treated cows was significantly (p<0.01) higher in treated lactation (2.5 ± 0.7) than in the previous lactation (2.2 ± 0.7). The average milk yield in all treated cows was significantly (p<0.01) higher than the control cows. Although, milk yields were higher in second parity than the first, there was no significant difference (p>0.05). The milk protein percentage was significantly higher (p<0.05) in treated group than the control group. Therefore, it may be concluded that periparturient anthelmintic treatment effectively reduced the gastrointestinal parasitic load and improved milk yield.